0787 Autonomic Dysfunction and Phenoconversion in Idiopathic/Isolated REM Sleep Behavior Disorder. (27th May 2020) - McCarter, S; Gehrking, T; St. Louis, E; Suarez, M; Boeve, B; Silber, M; Low, P; Singer, W
Abstract: Introduction: REM-sleep behavior disorder (RBD) is a common finding among patients with synucleinopathies. We aimed to determine the degree of autonomic dysfunction in patients presenting with idiopathic RBD (iRBD), and the predictive value of autonomic dysfunction for phenoconversion to a defined neurodegenerative disease. Methods: We searched our electronic medical record for patients diagnosed with iRBD who also underwent standardized autonomic function testing within 6 months of iRBD diagnosis, and who had clinical follow-up of at least 3 years following iRBD diagnosis. Patients who received a diagnosis of phenoconversion within 3 months of autonomic testing were excluded. The composite autonomic severity score (CASS) was derived and compared between phenoconverters and non-converters using chi-square and Wilcoxon rank-sum tests. Results: We identified 18 patients who fulfilled in- and exclusion criteria. Average age at autonomic testing was 67 ± 6.6 years. Twelve (67%) patients phenoconverted during the follow-up period; 6 developed PD, the other 6 DLB. Fifteen (83%) patients had at least mild autonomic dysfunction. There were no significant differences between overall converters and non-converters in total CASS or CASS subscores. However, iRBD patients who developed DLB had significantly higher total and cardiovagal CASS scores compared with those who developed PD (p <0.05), and a trend for higher adrenergic CASS scores compared to those who developed PD and those who did not phenoconvert (p=0.08 for each). Conclusion: Autonomic dysfunction was seen in 83% of iRBD patients, and more severe baseline cardiovagal and adrenergic autonomic dysfunction in iRBD was associated with phenoconversion to DLB but not PD. Prospective studies are needed to confirm the value of autonomic testing for predicting phenoconversion and disease phenotype in iRBD. Support: